The Effect Of Prices And Service Facilities On Loyalty Guests In Rooms Inc Hotel Semarang - Aulia Febrianika; Renny Aprilliyani; Enik Rahayu (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
The aim of this research is to determine and analyze theinfluence of price and facilities partially and jointly on guest loyalty at Rooms Inc Hotel Semarang and to determine the variables that most influence guest loyalty at Rooms Inc Hotel Semarang. This research uses a quantitative type of research. Quantitative research. The population in this study was 8,833 guests taken from data from November 2022 to December 2022 at Rooms Inc Hotel Semarang. The sample in this research was 100 respondents. Data collection techniques are questionnaires and observations. The analysis technique used in this research is multiple linear regression analysis. The results of the research state that price and facilities partially have a positive and significant effect on Rooms Inc. Hotel guest loyalty. Price and facilities jointly influence guest loyalty at Rooms Inc Hotel. The price variable is the variable that has the most influence on Rooms Inc Hotel guest loyalty